2011
DOI: 10.1089/met.2010.0045
|View full text |Cite
|
Sign up to set email alerts
|

Hip Circumference and Incident Metabolic Risk Factors in Chinese Men and Women: The People's Republic of China Study

Abstract: Background: The associations between adiposity and metabolic risk factors have been suggested to vary across ethnicities. Studies in Caucasians have shown that after adjusting for waist circumference and body mass index (BMI), a larger hip circumference may be protective for metabolic risk factors. To our knowledge, these associations have never been examined in a Chinese population. Methods: Baseline (1987)(1988) and follow-up (1993-1994) data were from the People's Republic of China Study (n ¼ 1,144 men, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…The same interpretation applies to MUAC and CC. These results agree with studies of adult populations [ 47 49 ]. WC, WHR and WHtR have been used as indicators of abdominal obesity [ 50 ] and are associated with adverse CV risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…The same interpretation applies to MUAC and CC. These results agree with studies of adult populations [ 47 49 ]. WC, WHR and WHtR have been used as indicators of abdominal obesity [ 50 ] and are associated with adverse CV risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…Large HC after adjusting for WC and BMI is protective for metabolic risk factors in Caucasians [11,23]. Contrarily, we observed reduced HC in underweight compared with normal weight traders and higher HC in overweight and obese traders than traders with normal weight (p < 0.05).…”
Section: Discussionmentioning
confidence: 50%
“…It appears that increased HC is a risk factor rather than protective factor in Nigerians. Studies have shown that adiposity and metabolic risk factors vary across ethnicities [13,23].…”
Section: Discussionmentioning
confidence: 99%
“…In a Swedish female cohort, larger hip circumference was associated with significantly fewer adverse health outcomes [ 16 ]. However this relation seems to be ethnicity dependent, since in an Asian-Chinese population larger hip circumference was associated with incident high triglycerides, low HDL-C, and multiple metabolic abnormalities [ 17 ]. In the absence of data on an Asian-Indian population, the data on Asian-Chinese persons may be considered of greater relevance to the present study, despite the considerable genetic diversity of Asian-Indians [ 18 ].…”
Section: Discussionmentioning
confidence: 99%